Multiple organ failure in septic patients - Bilevicius,Elizabeth (2001)
Multiple organ failure (MOF) is the main cause of death in ICUs, especially affecting septic patients. It is strongly related to number of systems with failure, type of system involved, risk factors such as age, previous chronic diseases, delayed or inadequate resuscitation, persistent infection, immune suppression, and others. The prognoses is worse for patients rather than in elective or emergency surgical patients. The objective of this article is to provide data from our university teaching hospital ICU related to the incidence of septic patients, the distribution of MOF, and distribution of failure among each of the organs. The mortality rate, relationship between mortality and age, and mortality and types of organs affected were evaluated. The main bacterial causes of sepsis were also identified. A retrospective evaluation was done of 249 patients admitted to the ICU in a 4 month period during 1999. Fifty four patients had sepsis diagnosed by ACCS/SCCM criteria. There were 37 men and 17 women; 24 medical and 30 post-surgical patients (9 after elective surgery and 21 emergency patients). APACHE II score was calculated on admission and MOF, measured for the first five days, was diagnosed using Marshall and Meakins criteria. The statistical method used was non-parametric Mann-Whitney test, p<0.05 was considered significant. The incidence of sepsis was recorded in 54/249 patients (22%). Thirty of these 54 patients (56%) died. Death occurred in 2 of 11 pateints with one organ failure (18%), in 14/27 with 2 or 3 organ failures (52%), and 14/16 with 4 or more organ failures (88%). None of the three patients 15 to 20 years old died, 17/32 (55%) pateints age 21-60 years, and >61 years 13/19 (68%), died. There were 23 patients with positive bacterial culture. The most frequent bacteria found were: Pseudomonas aeruginosa (5), multiresistant Acinetobacter baumanii (3), Staphylococcus epidermidis (3), Enterobacter aerogenes (3), Klebsiella pneumoniae (2) and multiresistant Staphylococcus aureus (2). The mean value ± SD of APACHE II (mortality risk) for survivors was 21 ± 18 and for non-survivors 42 ± 26 (p<0.001). We conclude that MOF due to sepsis in an ICU is frequent, with high mortality related to the number of failing organs, age and high APACHE II.